2019
DOI: 10.1155/2019/2835256
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle-Mediated Dendritic Cell Activation in Acinetobacter baumannii Clinical Isolate, which Contributes to Th2 Response

Abstract: Acinetobacter baumannii, as a nonfermentation Gram-negative bacterium, mainly cause nosocomial infections in critically ill patients. With the widespread of multidrug-resistant Acinetobacter baumannii, the urgency of developing effective therapy options has been emphasized nowadays. Outer membrane vesicles derived from bacteria show potential vaccine effects against bacterial infection in recent study. Our present research is aimed at investigating the mechanisms involved in immune protection of mice after out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Various biofilm associated factors such as OmpA, Bap, Ata, PNAG and outer membrane vesicles have been studied as promising vaccine candidates for immunization against A. baumannii ( Ahmad et al., 2016 ; L.V. Bentancor et al., 2012 ; Cai et al., 2019 ; Fattahian et al., 2011 ; Jun et al., 2013 ; Luo et al., 2012 ). Other preventive strategies, such as antibiofilm polymers and coated medical devices are attractive approaches as they can inhibit bacterial colonization and prevent biofilm formation by a broad range of Gram-positive and Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Various biofilm associated factors such as OmpA, Bap, Ata, PNAG and outer membrane vesicles have been studied as promising vaccine candidates for immunization against A. baumannii ( Ahmad et al., 2016 ; L.V. Bentancor et al., 2012 ; Cai et al., 2019 ; Fattahian et al., 2011 ; Jun et al., 2013 ; Luo et al., 2012 ). Other preventive strategies, such as antibiofilm polymers and coated medical devices are attractive approaches as they can inhibit bacterial colonization and prevent biofilm formation by a broad range of Gram-positive and Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] In a recent study, it was found that the outer membrane vesicle from an A. baumannii clinical strain could activate bone marrow-derived DC to promote Th2 activity. [ 42 ] In our study, the finding that a rapid accumulation and maturation of cDCs in the lung of mice with normal immunity after A. baumannii stimulation suggested that cDCs were involved in the immune response to A. baumannii .…”
Section: Discussionmentioning
confidence: 67%
“…The interplay between OMV-associated PAMPs and innate immune cells plays an important role through induction of proinflammatory cytokine secretion by different cell types ( 31 – 33 ). Among the important PRRs, Toll-like receptors (TLRs) are capable of detecting the PAMPs present on the OMVs ( Fig.…”
Section: Omvs and Interactions With Immune Systemmentioning
confidence: 99%